Education : Past, Present and Future Global Challenges - Patrinos, Harry Anthony; Psacharopoulos, George (2012)
Progress in educational development in the world since 1900 has been slow and uneven between countries. Providing basic education for all children in developing countries has been and remains an unmet challenge of governments and international organizations alike. This is in sharp contrast to recent findings in the economics literature on the catalytic role of human capital for economic growth and social development in general. Using a newly constructed matched data set on education and national accounts in the 1950 to 2010 period, this paper estimates the loss of income and equity associated with not having a faster rate of human capital accumulation, using alternative methodologies and specific country examples. Such loss is projected backward (1900-1950) and forward (2010-2050) using plausible assumptions regarding what countries could have done in the past or may do in the future to accelerate human capital formation. The findings suggest that the welfare loss in terms of per capita income conservatively ranges from about 7 to 10 percent. Improved educational attainment is also shown to have an effect in reducing income inequality.